2018
DOI: 10.1074/jbc.ra118.003194
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Pseudomonas aeruginosa NQR complex, a bacterial proton pump with roles in autopoisoning resistance

Abstract: is a Gram-negative bacterium responsible for a large number of nosocomial infections. The respiratory chain contains the ion-pumping NADH:ubiquinone oxidoreductase (NQR). This enzyme couples the transfer of electrons from NADH to ubiquinone to the pumping of sodium ions across the cell membrane, generating a gradient that drives essential cellular processes in many bacteria. In this study, we characterized NQR (Pa-NQR) to elucidate its physiologic function. Our analyses reveal that Pa-NQR, in contrast with NQR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 99 publications
5
36
0
Order By: Relevance
“…The most important physiologic difference between these enzymes is that complex I is a proton pump, while NDH-2 is not involved in ion pumping [17,23]. Although in many cases it has been reported that NQR acts as a sodium pump, we recently described that P. aeruginosa NQR is an ion pump that specifically transports protons [24]. This raises questions regarding the role of each of these enzymes, especially since NQR https://doi.org/10.1371/journal.pone.0231965.g001…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The most important physiologic difference between these enzymes is that complex I is a proton pump, while NDH-2 is not involved in ion pumping [17,23]. Although in many cases it has been reported that NQR acts as a sodium pump, we recently described that P. aeruginosa NQR is an ion pump that specifically transports protons [24]. This raises questions regarding the role of each of these enzymes, especially since NQR https://doi.org/10.1371/journal.pone.0231965.g001…”
Section: Introductionmentioning
confidence: 92%
“…P. aeruginosa NQR was purified as described previously [24]. Briefly, P. aeruginosa nqrA-F NQR operon was cloned in pBAD plasmid and transformed into Vibrio cholerae O395N1 Δnqr cells [38].…”
Section: P Aeruginosa Nqr Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria are known to coordinate the composition of the electron transport chain (ETC), and in particular, levels of the terminal oxidases, according to their metabolic needs [41]. The ETC of P. aeruginosa contains three NADH dehydrogenases; the multi-subunit proton pumping NDH-1 (encoded by nuoA-N (PA2637-PA2649)), the HQNO-resistant proton pump Nqr (encoded by nqrA-F (PA2994-2999)), and a single-subunit flavoenzyme which does not participate in ion translocation (NDH-2, encoded by ndh , PA4538) [42]. All three dehydrogenases displayed increased expression during growth on acetate, particularly at the protein level (file S1).…”
Section: Resultsmentioning
confidence: 99%
“…aeruginosa NADH:ubiquinone oxidoreductase (NQR) is actually a completely new form of proton pump, which plays an important role in the adaptation against autotoxicity during the infection process (Raba et al, 2018).…”
Section: Comparative Functional Enrichment Analysis Reveals Host-specmentioning
confidence: 99%